STORE ATMOSPHERE, e-WOM, QUALITY OF SERVICE AS A DETERMINANT OF PURCHASE DECISIONS AT COFFEE BUYERS - DJ, YR; Rosyad, S (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2022)
This study has a goal, namely to examine the influence of store atmosphere, e-WOM and service quality variables on purchasing decision variables at the Coffee Shop. This type of research is descriptive quantitative. The population is buyers at the Coffee Shop with 100 samples of respondents with accidental sampling technique. The results of the F test prove that there is a simultaneous influence of store atmosphere, e-WOM and service quality on purchasing decisions at the Coffee Shop where the Fcount > Ftable (44.532 > 2.70) and the significant value_0.00_<_,05. The results of the t-test test prove that store atmosphere has a positive and significant influence on purchasing decisions at Kedai Beli Kopi with a value of tcount > ttable (6.224 > 1.985) and a significant value of 0.000 <0.05. e-WOM has been proven to have a positive and significant effect on purchasing decisions at Kedai Beli Kopi with a value of tcount > ttable (2,739 > 1,985)_and the significant value is 0.007 < 0.05 ..Service quality is also proven to have a positive and significant effect on purchasing decisions at Kedai Beli Kopi with a value of tcount > ttable (2,078 > 1,985) and a significant value of 0.040 < 0.05.